Staff training for the purposes of marina management - Hącia, Ewa; Łapko, Aleksandra (Kształcenie kadr na potrzeby portów jachtowych, 2019)
The main purpose of the article is to present issues of staff training for the purposes of marina management. Particular attention was paid to training as a way to improve and develop marina employees. The problem was presented using the example of specialized training for marina employees and operators. It was prepared according to a training process – a procedure based on selected research techniques such as CAWI, nominal and interactive groups. Analysis of the entire training process presented in the article allowed for the formulation of conclusions. It was shown that there is a need to organize training courses for marina staff covering various thematic blocks in the training program consistent with the current situation and trends observed in nautical tourism
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 10, s. 176-186